Rural Futures: Development, Aspirations, Mobilities, Place, and Education. (14th March 2016) - Corbett, Michael
Abstract : This piece responds to the content of each of the articles in this issue and raises questions in response to some explicit and implicit themes including particularly the way that differently positioned rural youth are "oriented" in the course of their educational experience. These articles are read as accounts of people in place that confound and confront simplistic deficit assessments of educational paths, aspirations, relationships, and purposes in rural space. I suggest that this issue illustrates how rural education scholarship inevitably returns to the particular and to the material, challenging the hegemony of the placeless and abstracted neoliberal vision of education's aims in late modernity. The broad argument is that educational struggles and orientations in rural schools should be understood in relation to the crucial global challenges of sustainability and survival.